1995
DOI: 10.1111/j.1399-302x.1995.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of salivary proteins inhibiting herpes simplex virus 1 replication

Abstract: Salivary proteins play an important role in the maintenance of the oral ecology. Previous studies have indicated that human submandibular-sublingual and parotid salivas can selectively suppress the in vitro infectivity of herpes simplex virus 1. The purpose of this study was to identify the salivary components in human submandibular-sublingual saliva that modulate in vitro infectivity. Assessment of the interaction of viral particles with salivary components was accomplished using an in vitro solid-phase assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…These proteins may play a minor role in regulating salivary calcium (Shomers et al, 1982;Al-Hashimi and Levine, 1989;Lamkin and Oppenheim, 1993), but may act mainly as cysteine-proteinase inhibitors . Cystatins may inhibit bacterial proteases involved in the pathogenesis of periodontal disease, and they may also interfere with in vitro infection by herpes simplex virus (Gu et al, 1995). Another isoform, cystatin C, is present in both saliva and serum .…”
Section: (Ii) Salivary Proteins-microbial Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins may play a minor role in regulating salivary calcium (Shomers et al, 1982;Al-Hashimi and Levine, 1989;Lamkin and Oppenheim, 1993), but may act mainly as cysteine-proteinase inhibitors . Cystatins may inhibit bacterial proteases involved in the pathogenesis of periodontal disease, and they may also interfere with in vitro infection by herpes simplex virus (Gu et al, 1995). Another isoform, cystatin C, is present in both saliva and serum .…”
Section: (Ii) Salivary Proteins-microbial Interactionsmentioning
confidence: 99%
“…This reveals a cryptic epitope (cryptitope) which may promote the adherence of many oral bacteria, including streptococci (Gibbons et al, 1991), actinomyces species (Gibbons et al, 1988), and Porphyromonas gingivalis (Amano et al, 1994). bPRP functions are less well-known, but a recent study suggests that they may inhibit the infectivity of herpes simplex virus (Gu et al, 1995). Statherin is a small phosphoprotein which may play a primary role in maintaining calcium equilibrium (Hay et al, 1984).…”
Section: (Ii) Salivary Proteins-microbial Interactionsmentioning
confidence: 99%
“…Less desirable is the ability of APRPs to mediate binding of bacteria to hydroxyapatite, since it may assist in the formation of dental plaque (Gibbons et al ., 1988;Kataoka et al ., 1997). BPRPs have anti-viral activity (Gu et al ., 1995) and bind to C. albicans (O'Sullivan et al ., 1997), which may affect the colonization of oral surfaces by these micro-organisms.…”
Section: (B) P Roline -Richproteinsmentioning
confidence: 99%
“…Björck et al (1990) showed that human recombinant cystatin C inhibited HSV-1 replication in green monkey kidney cells. In addition, proline-rich proteins and salivary cystatins were able to inhibit HSV-1 replication (Gu et al, 1995). In contrast, the level of cystatins in saliva did not correlate with HSV-neutralizing activity (Välimaa et al, 2002).…”
mentioning
confidence: 99%
“…In addition to their other biological functions, cystatins have been shown to inhibit RNA virus-induced programmed cell death (Björklund et al, 1997). Moreover, the antiviral properties of cystatins (Björck et al, 1990;Aoki et al, 1995;Gu et al, 1995;Collins & Grubb, 1998) suggest that they may also inhibit cysteine proteases used by viruses during infection.…”
mentioning
confidence: 99%